1993
DOI: 10.1259/dmfr.22.4.8181644
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of periapical and detailed narrow-beam radiography for diagnosis of periapical bone lesions.

Abstract: The diagnostic performance of the detailed narrow-beam (DNB) technique of the Scanora multimodal radiography system was compared for periapical radiography for the detection of periapical bone lesions at 262 dental sites in 144 patients. Receiver operating characteristics (ROC) of both imaging modalities were analysed in relation to the ratings of five observers for the whole dentition, three dental regions, and two types of periapical lesions. ROC analysis demonstrated no overall or regional significant diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 10 publications
0
10
0
1
Order By: Relevance
“…For periapical radiography, our intra-observer agreement rates accord with those found in most previous studies 4 ' 21 ' 23 ' [25][26][27] . Intra-observer agreement rates for multiview and stereoscopic zonography were also slightly lower than those for multiview DNB radiography 4 . The difference might be explained by the fact that the observers were familiar with the DNB technique, because the imaging principle of DNB radiography is similar to panoramic radiography.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…For periapical radiography, our intra-observer agreement rates accord with those found in most previous studies 4 ' 21 ' 23 ' [25][26][27] . Intra-observer agreement rates for multiview and stereoscopic zonography were also slightly lower than those for multiview DNB radiography 4 . The difference might be explained by the fact that the observers were familiar with the DNB technique, because the imaging principle of DNB radiography is similar to panoramic radiography.…”
Section: Discussionmentioning
confidence: 63%
“…In detailed dento-alveolar imaging using the Scanora® unit, diagnostic information is gathered from each dental region selectively, using multiple projections and magnification. We found, in a previous study 4 , that detailed narrow-beam (DNB) radiography revealed 18% more periapical lesions than periapical radiography, when this technique was used to supplement the information obtained from a panoramic radiograph. In DNB radiography, tomographic blurring is achieved by rotational scanning, in zonography by using spiral movement 1 .…”
mentioning
confidence: 89%
See 3 more Smart Citations